2013
DOI: 10.1103/physrevlett.111.106804
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Control of Noncollinear Magnetic Order in Nickel Oxide Heterostructures

Abstract: We have used resonant x-ray diffraction to develop a detailed description of antiferromagnetic ordering in epitaxial superlattices based on two-unit-cell thick layers of the strongly correlated metal LaNiO3. We also report reference experiments on thin films of PrNiO3 and NdNiO3. The resulting data indicate a spiral state whose polarization plane can be controlled by adjusting the Ni d-orbital occupation via two independent mechanisms: epitaxial strain and spatial confinement of the valence electrons. The data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
116
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(125 citation statements)
references
References 36 publications
8
116
1
Order By: Relevance
“…Instead, DFT studies on (001) SLs indicate that both e g states contribute to the Fermi surface [9][10][11] . Nevertheless, these (001) SLs have proven to be a fruitful playground to explore lowdimensional phenomena such as a MIT due to confinement and Coulomb interaction [11][12][13][14][15][16] . The possibility of topologically nontrivial behavior is currently shifting the interest from the much studied (001) stacking of AO/BO 2 planes to the (111)-perovskite superlattices with a B/AO 3 sequence.…”
mentioning
confidence: 99%
“…Instead, DFT studies on (001) SLs indicate that both e g states contribute to the Fermi surface [9][10][11] . Nevertheless, these (001) SLs have proven to be a fruitful playground to explore lowdimensional phenomena such as a MIT due to confinement and Coulomb interaction [11][12][13][14][15][16] . The possibility of topologically nontrivial behavior is currently shifting the interest from the much studied (001) stacking of AO/BO 2 planes to the (111)-perovskite superlattices with a B/AO 3 sequence.…”
mentioning
confidence: 99%
“…16,17 It was also demonstrated that both strain and dimensional confinement can drive an LNO film towards a spin-density-wave state, which is similar to what is observed in the insulating phase of other nickelates. 18 This makes LaNiO 3 a very suitable system for materials design by strain engineering and heterostructuring.…”
Section: Introductionmentioning
confidence: 99%
“…directly correlates to the material's resulting properties. [1][2][3][4][5] For example, systems such as the manganites (colossal magnetoresistance), 6 the cobaltates (spin-state transitions), 7,8 and the cuprates (hightemperature superconductivity) 9,10 owe their behaviors to specific configurations of the electronically active transition-metal cation d orbitals, which, for near-cubic symmetry, are split into the (lower energy) t 2g and (higher energy) e g orbitals. The development of atomically precise growth techniques for oxides has opened up the possibility of controlling orbital configurations via layered heterostructures.…”
Section: Introductionmentioning
confidence: 99%